A STUDY ON RAPIDO’S STRATEGIES TO ENSURE SUCCESS AND SUSTAINABILITY (International Journal of Food and Nutritional Sciences, 2022)
Travelling has always been a necessity and in today’s era its importance has grown enormously. One of the major issues faced by the travel industry is sustainability. In today’s time, being a successful and sustainable firm at the same time is very difficult. Rapido, founded in November 2015, came up as one such firm in a highly competitive market by ensuring quality services to its customers and maintaining sustainability. It has added value to the passenger commuting sector This study aims to analyse the factors involved in Rapido’s success and the firms’ level of sustainability.